Evaluation of the radiographic liver length/11th thoracic vertebral length ratio as a method for quantifying liver size in cats. Issue 6 (30th August 2019) - An, Gayeon; Kwon, Dohoon; Yoon, Hyounglok; Yu, Jin; Bang, Sohyun; Lee, Youngjae; Jeon, Seokho; Jung, Jaihyun; Chang, Jinhwa; Chang, Dongwoo
Abstract: Abdominal radiography is a standard diagnostic test for cats with suspected liver disease, however, absolute measurements of radiographic liver size can be affected by other factors such as positioning, radiographic technique, and obesity. This prospective and retrospective, analytical, cross‐sectional study evaluated the liver length/11th thoracic vertebral length (LL/T11) ratio as a method for minimizing these outside effects. In a prospectively recruited sample of 25 clinically healthy cats, measurements of radiographic LL/T11 ratio were compared with CT measurements of liver volume. Effects of radiographic technical factors (body posture, recumbency state, and beam center to LL/T11 ratio) and observer were also tested. In a retrospectively recruited sample of 324 cats with no evidence of liver disease, radiographic measurements of the LL/T11 ratio were performed using right lateral radiographs and compared among signalment groups (age, sex, body weight, and body condition score). There was a strong significant correlation between the LL/T11 ratio and CT liver volume ( P  < .001), and this ratio was not affected by radiographic technical factors. The reference value of the LL/T11 ratio was 4.22 ± 0.54 and the LL/T11 ratio did not differ among signalment groups. Findings supported the use of the LL/T11 ratio as a novel quantitative index of radiographic liver size in cats. Future studies in clinically affected cats are needed to further validate this method.